Low cost CaCl2 pretreatment of sugarcane bagasse for enhancement of textile dyes adsorption and subsequent biodegradation of adsorbed dyes under solid state fermentation - Kadam, Avinash A.; Lade, Harshad S.; Patil, Swapnil M.; Govindwar, Sanjay P. (Bioresource technology, 2013)
[Display omitted] ► Dye adsorption capacity of SCB was enhanced by using different pretreatments. ► Among pretreatments studied CaCl2 pretreated SCB shows maximum adsorption capacity. ► Adsorbed dyestuff on CaCl2 pretreated SCB was decolorized under SSF using Providensia stuarti. ► Tray bioreactor was studied for decolorization of adsorbed dyes on CaCl2 treated SCB. ► Analysis of product carried out using FTIR, HPLC and HPTLC confirmed degradation. Pretreatments to sugarcane bagasse (SCB) such as CaCl2, alkali, ammonia, steam and milling showed 91%, 46%, 47%, 42% and 56% adsorption of Solvent Red 5B (SR5B); 92%, 57%, 58%, 56% and 68% adsorption of simulated dyes mixture (SDM), and 86%, 45%, 49%, 44% and 56% adsorption of a real textile effluent (RTE), respectively. However, the untreated SCB showed 32%, 38% and 30% adsorption of SR5B, SDM and RTE, respectively. Adsorption of SR5B on CaCl2 pretreated SCB follows pseudo-second order kinetics. SEM and FTIR analysis reveals the delignification of CaCl2 pretreated SCB. SR5B, SDM and RTE adsorbed on CaCl2, alkali, ammonia, steam and milling pretreated SCB were decolorized under solid state fermentation using isolated Providensia staurti strain EbtSPG. Tray bioreactor study showed 86% American Dye Manufacturers Institute (ADMI) removal of RTE in 72h. Biodegradation of adsorbed SR5B was confirmed using FTIR, HPLC and HPTLC.